Fashion and social distinction signs in the life of a uruguayan artist (Revista de Ensino em Artes, Moda e Design, 2021)
The article analyzes a set of images, from photographs to photographic reproductions inthe Uruguayan and Brazilian journals such as Anales: Revista Mensual Ilustrada, MundoUruguayo, O Cruzeiro, and O Jornal. These images are indications of the artistic trajectoryof the Uruguayan Raquel Aliseris Bernadá [de Labaure-Casaravilla] (1923-1986) froma photo in which she appears with the laureate work “Patos Pekineses” from the SalónNacional in 1938, a porteño exhibition, her presence in European museums where shemade copies of renowned works, attending parties until getting married in Montevideo. Theimages reveal this artist’s trajectory with signs of social distinction and identify the fashionand the appearance culture. The turning point is the wedding. The bride is represented inthe Montevideo newspapers within the tradition with touches of modernity, with a satin dress,veil, wreath and original bouquet. The research showed an artist committed to her art anddressed with sobriety and elegance in places of artistic sociability. On the other hand, sheis seen by the Rioplatense and Brazilian press as a socialite, with clothes denoting socialdistinction and according to fashion trends.
Keywords: Artist; fashion; press